Pseudoamycle Polylepisae Gen. Et Sp. Nov., a Fulgorid from the Highlands of Northern Chile (Hemiptera: Fulgoridae) - Fierro-Tapia, C (Magnolia Press, 2019)
Pseudoamycle polylepisae gen. et sp. nov. is described from northernmost Chile (Arica and Parinacota Region). It is characterized by the small and brown body, head with no preocular flange, cephalic process porrect and dorsoventrally compressed, dorsal surface from lateral view not angulate at level of eyes, eyes round, tegmina concolorous and vein MP of tegmen pectinate. The new taxon was found to be associated with Polyepis rugulosa Bitter (Rosaceae). Copyright © 2019 Magnolia Press